The Process of Preparing Irish Cello Sonatas (1968-1996) for Performance - Cleary, Annette (Royal Irish Academy of Music, 2016)
This dissertation focuses on all the sonatas for cello and piano by Irish composers in the second half of the twentieth century. The sonatas, seven in total, were composed between 1968 and 1996 and show little similarity to each other. For the performer, challenges are presented in preparing these works for performance. Apart from the premiere performance only one of these sonatas was subsequently performed and five of the scores are unpublished. There are almost no readily available recordings which could serve as a guide. Therefore the performer needs to rely on a variety of interpretative skills to create a valid realisation of these sonatas. The interpretative skills required are based on three different approaches: the cognitive, the physical and the intuitive. Solo performers face both technical and musical challenges in the process of preparing a work for public performance. Although a musical interpretation of a particular work may be formed prior to the initial performance, it is only within performance that further knowledge is gained, which then informs subsequent performances. This dissertation discusses the cognitive, the physical and the intuitive aspects of performance preparation within the framework of the cello sonatas, with examples drawn from these works to illustrate performance decisions. A performer’s commentary is included and, where possible, collaboration with the composers is integrated in the discussion. This will provide a resource for those who wish to carry out further research or to perform this repertoire.
Keywords: Music; Sonatas (Cello and piano); Sonatas (Cello and piano) - 20th century - Ireland; Performance practice (Music)